Indigenous Starter Cultures to Improve Quality of Artisanal Dry Fermented Sausages from Chaco (Argentina) - Noelia Z. Palavecino Prpich; Marcela P. Castro; María E. Cayré; Oscar A. Garro; Graciela M. Vignolo (International Journal of Food Science)
Lactic acid bacteria (LAB) and coagulase negative cocci (CNC) were isolated from artisanal dry sausages sampled from the northeastern region of Chaco, Argentina. In order to evaluate their performance in situ and considering technological features of the isolated strains, two mixed selected autochthonous starter cultures (SAS) were designed: (i) SAS-1 (Lactobacillus sakei 487 + Staphylococcus vitulinus C2) and (ii) SAS-2 (L. sakei 442 + S. xylosus C8). Cultures were introduced into dry sausage manufacturing process at a local small-scale facility. Microbiological and physicochemical parameters were monitored throughout fermentation and ripening periods, while sensory attributes of the final products were evaluated by a trained panel. Lactic acid bacteria revealed their ability to colonize and adapt properly to the meat matrix, inhibiting the growth of spontaneous microflora and enhancing safety and hygienic profile of the products. Both SAS showed a beneficial effect on lipid oxidation and texture of the final products. Staphylococcus vitulinus C2, from SAS-1, promoted a better redness of the final product. Sensory profile revealed that SAS addition preserved typical sensory attributes. Introduction of these cultures could provide an additional tool to standardize manufacturing processes aiming to enhance safety and quality while keeping typical sensory attributes of regional dry fermented sausages.